Peranan Manajemen Puncak, Wakil Manajemen, dan Konsultan dalam Tahap Awal Penerapan Sistem Manajemen Mutu - I Nyoman Sutapa (Institute of Research and Community Outreach - Petra Christian University, 2012)
The success of implementing the quality management system (QMS) ISO 9001:2008 for the family companies that applying in the initial stage will be the beginning of the strategic competitiveness. To develop, implement, control, and improve the QMS, it required roles, responsibilities, and sufficient authority for implementing actors. In this study, five hypotheses put forward by processing 30 data samples from the two companies of truck and bemo, and motorcycle parts’s company. The results of hypothesis testing showed the successful application of SMM in the family companies that already implementing QMS in the initial stage, significantly influenced by the roles, responsibilities, and authority from top management, and bridged with the role and tasks of the management representative and companion consultant.